Multicentric human papillomavirus–associated head and neck squamous cell carcinoma. Issue 2 (20th March 2014) - Caley, Andrew; Evans, Mererid; Powell, Ned; Paleri, Vinidh; Tomkinson, Alun; Urbano, Teresa Guerrero; Jay, Amrita; Robinson, Max; Thavaraj, Selvam
ABSTRACT Background The purpose of this study was to present the clinicopathological features of a series of patients with human papillomavirus (HPV)‐associated head and neck second primary tumors. Methods Patients with HPV‐associated head and neck second primary tumors from 3 centers were identified. HPV infection was evaluated using p16 by immunohistochemistry (IHC), high‐risk HPV DNA by in situ hybridization (ISH), and HPV genotyping by DNA polymerase chain reaction (PCR) enzyme immunoassay (EIA). Results Eleven patients were identified: 5 with synchronous and 6 with metachronous HPV‐positive second primary tumors, the latter demonstrating a mean time interval of 5 years. There were 13 second primary tumors: 11 oropharyngeal, 1 nasopharyngeal, and 1 floor of the mouth. Nine of 10 genotyped patients harbored HPV‐16, and 1 patient had HPV‐33 in 3 synchronous tumors. Conclusion HPV‐associated second primary tumors may present as synchronous and/or metachronous lesions and can arise outside the oropharynx after prolonged intervals. Further work is necessary to identify patients at risk and to elucidate the mechanisms of HPV‐associated head and neck second primary tumors. © 2014 Wiley Periodicals, Inc. Head Neck37: 202‐208, 2015